The nurses : a year of secrets, drama, and miracles with the heroes of the hospital - Robbins, Alexandra, 1976- (Workman Publishing, 2015)
In a gripping, behind-the-scenes look filled with drama, miracles, heartbreak, humor and unsung heroism, an award-winning journalist chronicles a year in the lives of four real-life hospital nurses, in a book that doubles as a shocking, unedited examination of our healthcare system.